Analisa Keakurasian Mesin CNC (Computer Numerical Control) Laser Cutting CO2 pada Persumbuan X dan Y - Lailiah, Azizatul; Heryana, Ghany; Suriaman, Irwan (Journal of Applied Mechanical Technology, 2023)
The development of computer technology has progressed very rapidly. CNC (Computer Numerical Control) machines have come a long way in the last few decades. CNC (Computer Numerical Control) machines were first introduced in the 1960s, and have undergone technological changes and improvements since then. A machine tool is very susceptible to inaccuracies resulting in a machine that is used for a long time and repeatedly can result in its feeding process. The deviating feeding process will greatly affect the quality of the workpiece. The purpose of this study was to determine the calibration process of CO2 CNC Laser Cutting Machines on the X and Y axes and the results for making machine feasibility decisions. The dial indicator tool will be used to determine the calibration results on a 2-axis CO2 Laser Cutting CNC machine for CO2 Laser Cutting. This CO2 CNC Laser Cutting Machine will be calibrated on each axis, namely the X and Y axes.